Stratal composition and stratigraphic organization of stratal elements in an ancient deep‐marine basin‐floor succession, Neoproterozoic Windermere Supergroup, British Columbia, Canada. Issue 1 (20th September 2015) - Terlaky, Viktor; Rocheleau, Jonathan; Arnott, Robert William Charles
Abstract: Despite a globally growing seismic and outcrop analogue data set, the detailed (centimetre to decametre) internal stratal make up of deep‐marine basin‐floor 'channelized‐lobe' strata remain poorly known. An ancient analogue for modern, mixed‐sediment, passive margin, deep‐marine basin‐floor fans is the well‐preserved Neoproterozoic Upper and Middle Kaza groups in the southern Canadian Cordillera. This succession is a few kilometres thick and comprises six sedimentary facies representing deposition from different kinds of sediment‐gravity flows. Representative lateral and vertical assemblages of one or more of these facies comprise six stratal elements, including: isolated scours, avulsion splays, feeder channels, distributary channels, terminal splays, and distal and off‐axis fine‐grained turbidite units. The internal characteristics of the various stratal elements do not differ from more distal to more proximal settings, but the relative abundance of the various stratal elements does. The difference in relative abundance of stratal elements in the kilometre‐scale stratigraphy of the Kaza Group results in a systematic upward change in architecture. The systematic arrangement of the stratal elements within the interpreted larger bodies, or lobes, and then lobes within the basin‐floor fan, suggests a hierarchical organization. In this article a hierarchy is proposed that is based on avulsion but, also importantly, the location of avulsion. The proposed avulsion‐based hierarchical scheme will be a useful tool to bridge the scalar gap between outcrop and seismic studies by providing a single stratigraphic framework and terminology for basin‐floor stratal elements.